(untitled) (Fiep Bulletin - online, 2013)
This study aimed at large, establish a timeline of the Brazilian Paraesport of income, examining its historical evolution from its inception until the present day, compared considering its structure in relation to the international structure. We used data from the Brazilian Paralympics Committee - CPB as main sources of information, the literature now exists on the national and international paraesport and questionnaires with people involved directly or indirectly with the paraesport (athletes, managers, technicians, functional classifiers, professionals in medical, psychological and nutritional areas) acting for over ten years in the Paralympic area. It was found that in Brazil, the sport practiced by people with disabilities - PCDs, the paraesport, had its beginning from 1958 and is administered today with autonomy of the CPB. From the beginning of the twenty-first century, a process of significant achievements was installed, resulting in the increase in the number of Paralympics medals. The process of validating the content of the historical timeline of Brazilian paraesport appointed five periods of income distributed since the nineteenth century to the twenty-first century: 1º. Unawareness about Brazilian Parasports; 2º. Discovery and Value of Brazilian Parasports; 3º. Specific Establishment of Brazilian Parasports; 4º. Divulgation of Performance Parasports through the Media; 5º Affirmation and Consolidations of Performance Parasports: Income and High Yield. With its own identity paraesport developed the specific arrangements tailored to the needs of its practitioners reflecting the values of culture to which he belongs. The management of such practices developed specialized levels and categories for competitions, reinforcing their identity. However, the registration process of the Paralympics activities still lacks a process of maturation and vocational training of professionals in this specific type of Paralympics activity.